PEDAGOGICAL ADVANTAGES OF VISUAL PROGRAMMING ENVIRONMENTS (VPE) IN THE DEVELOPMENT OF ALGORITHMIC THINKING - Saparova, Aysanem Ajiniyazovna (SCIENCE and SOCIETY, 2026)
This article is devoted to the study of the pedagogical potential of visual programming environments (VPE) in the development of algorithmic thinking. At the same time, the article provides recommendations on methods for integrating VPE into the educational process and its limitations.